Extending means-end theory through an investigation of the consumer benefit/price sensitivity relationship in two markets (the UK and Germany) - Baker, Susan (Cranfield University, 1996)
This research study is located in the field of consumer behaviour. It positions means-end theory in the interpretivist philosophical tradition and follows a cognitive approach to understanding purchase motivation. The thesis reports on the collection of empirical data to examine the relationship between consumer benefit and price sensitivity as a way of extending means-end theory. The subjects are purchasers of women's fine. fragrances _and trainers, in the UK and Germany. The literature review covers values research, in which means-end theory is contrasted with the macro approach, and price sensitivity, where the advantages of using the price sensitivity mechanism are discussed. The fieldwork is presented as a three-part process. In the pilot stage, constructs for laddering interviews and basic price sensitivity data were elicited from purchasers of the two product categories across the two markets.. The results of the second stage, in-depth interviews are reported as Ä± hierarchical value maps (produced manually) and price sensitivity charts (produced using' Lotus 1-2-3). Stage three involved a large scale survey carried out in both markets and this is then reported along with the results of the final analysis (produced using SPSS). `,' iii Notwithstanding poor response rates among the German samples, the findings support the first research proposition that there is a relationship between consumer benefit and. price sensitivity. The correlation results reveal that a high level of benefit is associated with low price sensitivity among purchasers of trainers in the UK (with a near zero correlation recorded for the German sample). In the case of perfume, a high level of benefit is shown to be associated. with high price sensitivity. Implications of the findings are discussed with reference to both marketing theory and practice. Finally, the strengths and weaknesses of the research design are reviewed, followed. by' the presentation of 14 items for future research.